Metallothionein-3 modulates the amyloid β endocytosis of astrocytes through its effects on actin polymerization. Issue 1 (December 2015) - Lee, Sook-Jeong; Seo, Bo-Ra; Koh, Jae-Young
Abstract Background Astrocytes may play important roles in the pathogenesis of Alzheimer's disease (AD) by clearing extracellular amyloid beta (Aβ) through endocytosis and degradation. We recently showed that metallothionein 3 (Mt3), a zinc-binding metallothionein that is enriched in the central nervous system, contributes to actin polymerization in astrocytes. Because actin is likely involved in the endocytosis of Aβ, we investigated the possible role of Mt3 in Aβ endocytosis by cortical astrocytes in this study. Results To assess the route of Aβ uptake, we exposed cultured astrocytes to fluorescently labeled Aβ1–40 or Aβ1–42 together with chloropromazine (CP) or methyl-beta-cyclodextrin (MβCD), inhibitors of clathrin- and caveolin-dependent endocytosis, respectively. CP treatment almost completely blocked Aβ1–40 and Aβ1–42 endocytosis, whereas exposure to MβCD had no significant effect. Actin disruption with cytochalasin D (CytD) or latrunculin B also completely blocked Aβ1–40 and Aβ1–42 endocytosis. Because the absence ofMt3 also results in actin disruption, we examined Aβ1–40 and Aβ1–42 uptake and expression inMt3 −/− astrocytes. Compared with wild-type (WT) cells, Mt3 −/− cells exhibited markedly reduced Aβ1–40 and Aβ1–42 endocytosis and expression of Aβ1-42 monomers and oligomers. A similar reduction was observed in CytD-treated WT cells. Finally, actin disruption andMt3 knockout each increased the overall levels of clathrin and the associated protein phosphatidylinositol-binding clathrin assembly protein (PICALM) in astrocytes. Conclusions Our results suggest that the absence ofMt3 reduces Aβ uptake in astrocytes through an abnormality in actin polymerization. In light of evidence that Mt3 is downregulated in AD, our findings indicate that this mechanism may contribute to the extracellular accumulation of Aβ in this disease.